2018
DOI: 10.3389/fpls.2018.01213
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Endophyte Alternaria tenuissima Can Affect Growth and Selenium Accumulation in Its Hyperaccumulator Host Astragalus bisulcatus

Abstract: Endophytes can enhance plant stress tolerance by promoting growth and affecting elemental accumulation, which may be useful in phytoremediation. In earlier studies, up to 35% elemental selenium (Se0) was found in Se hyperaccumulator Astragalus bisulcatus. Since Se0 can be produced by microbes, the plant Se0 was hypothesized to be microbe-derived. Here we characterize a fungal endophyte of A. bisulcatus named A2. It is common in seeds from natural seleniferous habitat containing 1,000–10,000 mg kg-1 Se. We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…However, further characterization of the proteins is needed, to confirm their role in selenium accumulation. Previously high fractions (up to 35% of all selenium) of elemental reduced Se 0 has been reported in roots of Astragalus bisulcatus (Fabaceae), which was suggested to be produced by microbial endophytes (Lindblom et al 2012, Lindblom et al 2018). Reduced Se 0 was observed especially in the A. bisulcatus nodules and roots inoculated with Se 0 -producing fungi Alternaria astragali or A. tenuissima.…”
Section: Discussionmentioning
confidence: 99%
“…However, further characterization of the proteins is needed, to confirm their role in selenium accumulation. Previously high fractions (up to 35% of all selenium) of elemental reduced Se 0 has been reported in roots of Astragalus bisulcatus (Fabaceae), which was suggested to be produced by microbial endophytes (Lindblom et al 2012, Lindblom et al 2018). Reduced Se 0 was observed especially in the A. bisulcatus nodules and roots inoculated with Se 0 -producing fungi Alternaria astragali or A. tenuissima.…”
Section: Discussionmentioning
confidence: 99%
“…halophiles and extremophiles). As an example, certain Astragalus taxa can hyperaccumulate selenium, and recent research has suggested that these plants may harbour unusual endophytic taxa that could influence selenium uptake (Sura‐de Jong et al ., ; Lindblom et al ., , ). Following a similar rationale, we also suggest surveying those plant families that are phylogenetically distinctive.…”
Section: Discussionmentioning
confidence: 99%
“…When grown on high Se dosage media, Penicillium expansum, Aureobasidium pullulans, Mortierella humilis, and Phoma glomerata all exhibit a similar phenotype [30,32]. This could be because when certain fungi reduce elemental selenium from inorganic sodium selenite [4,12], the hyphal matrix provides sites for the resulting Se nanoparticles [32]. Selenium is also incorporated into other biological macromolecules, including proteins [33].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available scientific research on selenium’s effect on fungal properties are focused on growth [ 2 ], morphology [ 4 , 5 ], antioxidation [ 6 8 ], selenium metabolomics [ 3 , 9 ], and chemical compounds [ 6 , 10 , 11 ]. In general, selenium tolerance is often associated with the accumulation of organic Se in certain fungi [ 12 ]. Previously, the selenium-tolerance mechanism of microorganisms has been investigated using genomic [ 13 ], proteomics [ 14 ], and metabolomic analysis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation